The Concept of Student’s Comfort on Islamic Boarding School - Nurfitri Nurfitri; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Theraphy, 2020)
Comfort in Islamic boarding schools is the most important thing for students to be able to survive and follow the process of teaching and learning actively and optimally. For this reason, the role of guidance and counseling teacher is very much needed in helping to improve the comfort of students by applying guidance and counseling services. The article will try to explain about the convenience of students in Islamic boarding schools and their implications in guidance and counseling services. Furthermore this article will explain matters related to understanding of comfort, aspects of comfort, factors that affect comfort, psychological problems of students in Islamic boarding schools, the role of counselors in boarding schools and the implications in guidance and counseling services.